2015
DOI: 10.1182/blood-2014-11-610816
|View full text |Cite
|
Sign up to set email alerts
|

Hemophagocytic lymphohistiocytosis caused by dominant-negative mutations in STXBP2 that inhibit SNARE-mediated membrane fusion

Abstract: Key Points Monoallelic STXBP2 mutations affecting codon 65 impair lymphocyte cytotoxicity and contribute to hemophagocytic lymphohistiocytosis. Munc18-2R65Q/W mutant proteins function in a dominant-negative manner to impair membrane fusion and arrest SNARE-complex assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
81
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 41 publications
(79 reference statements)
8
81
0
Order By: Relevance
“…Previous studies have suggested that Munc18-2 can interact with the monomeric Syntaxins STX3 (39,40), STX2 (41), and STX11 (13,(33)(34)(35). However, other SM proteins have distinct binding modes in which they engage either monomeric syntaxins or SNARE complexes (42-45).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that Munc18-2 can interact with the monomeric Syntaxins STX3 (39,40), STX2 (41), and STX11 (13,(33)(34)(35). However, other SM proteins have distinct binding modes in which they engage either monomeric syntaxins or SNARE complexes (42-45).…”
Section: Resultsmentioning
confidence: 99%
“…Munc18-2 R65Q is a recently described disease-associated mutant that displayed stronger binding to STX11 and inhibits membrane fusion in vitro and in vivo in a dominant-negative manner (33). Addition of Munc18-2 R65Q to the flipped SNARE fusion assay with STX11-GPI drastically reduced both lipid mixing and complete fusion ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some monoallelic mutations may also potentially act in a dominant-negative manner. 39 It is probably too early to be able to appreciate the exact relevance of polygenic inheritance in the secondary forms of HLH. Few retrospective studies reported in some patients the presence of deleterious monoallelic mutations in one or two HLH genes, among the few analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Some mutations may even display dominant negative effects, which are determined through advanced cellular assays. 8 Second, with less severe impairments in lymphocyte cytotoxicity, environmental factors play an increasing role in determining HLH susceptibility. 3 Nonetheless, the concept of gene dosages in determining the efficacy of target cell killing may have wider implications for the risk of developing a spectrum of diseases associated with impaired lymphocyte cytotoxicity.…”
mentioning
confidence: 99%